2013
DOI: 10.1111/mec.12221
|View full text |Cite
|
Sign up to set email alerts
|

When bugs reveal biodiversity

Abstract: One of the fundamental challenges of conservation biology is gathering data on species distribution and abundance. And unless conservationists know where a species is found and in which numbers, it is very difficult to apply effective conservation efforts. In today's age of increasingly powerful monitoring tools, instant communication and online databases, one might be forgiven for thinking that such knowledge is easy to come by. However, of the approximately 5,400 terrestrial mammals on the IUCN Red List, no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 14 publications
0
22
0
1
Order By: Relevance
“…Advances in non‐invasive survey methods and statistical modelling techniques provide ways to address these challenges. Two non‐invasive methods have revolutionized surveys for tropical mammals: camera‐traps (Tobler, Carrillo‐Percastegui, Pitman, Mares, & Powell, ) and high‐throughput sequencing of environmental DNA (eDNA) (Bohmann, Schnell, & Gilbert, ). Camera‐trapping is a well‐established method and has been used to gather data on even the rarest of tropical mammal species (Ganas & Lindsell, ; Raloff, ; Whitfield, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Advances in non‐invasive survey methods and statistical modelling techniques provide ways to address these challenges. Two non‐invasive methods have revolutionized surveys for tropical mammals: camera‐traps (Tobler, Carrillo‐Percastegui, Pitman, Mares, & Powell, ) and high‐throughput sequencing of environmental DNA (eDNA) (Bohmann, Schnell, & Gilbert, ). Camera‐trapping is a well‐established method and has been used to gather data on even the rarest of tropical mammal species (Ganas & Lindsell, ; Raloff, ; Whitfield, ).…”
Section: Introductionmentioning
confidence: 99%
“…Large-and medium-sized mammals tend to be particularly vulnerable to hunting because they often occur at lower average population densities and have lower intrinsic rates of increase and longer generation times (Bodmer, Eisenberg, & Redford, 1997;Cardillo et al, 2005;Davidson, Hamilton, Boyer, Brown, & Ceballos, 2009). Indeed, the "empty forest syndrome" that Redford (1992) warned about almost three decades ago is now a commonplace phenomenon and, given the ever-increasing demand for wildlife products in the world's tropical regions (Rosa et al, 2016;Ripple et al, 2016), this trend is unlikely to slow in the coming years.…”
Section: Introductionmentioning
confidence: 99%
“…This combines VEM with invertebrate-derived DNA (iDNA), a term designating the genetic material ingested by invertebrates feeding on vertebrates [77]. Several studies have shown that iDNA from a variety of vertebrate species can be identified from field-caught animals, including mosquitoes [78,79], carrion flies [59,60,80], biting midges [81], leeches [71,82] and ticks [83]. For the identification of host DNA from arthropod blood meals, PCR-based or serological techniques are traditionally used [84,85,86,87,88].…”
Section: Combining Vem With Idnamentioning
confidence: 99%
“…) or contained by invertebrates feeding on vertebrates (iDNA; Bohmann et al . ; Calvignac‐Spencer et al . ,b; Schnell et al .…”
Section: Introductionmentioning
confidence: 99%
“…Novel sources of DNA allowing for a broad screening of local mammalian biodiversity with reduced costs and effort have recently been identified. Specifically, great potential is seen in the use of DNA gathered from the environment (eDNA; Taberlet et al 2012) or contained by invertebrates feeding on vertebrates (iDNA; Bohmann et al 2013;Calvignac-Spencer et al 2013a,b;Schnell et al 2012). In one of the latter proof of principle studies, Calvignac-Spencer and coworkers focused on blow and flesh flies (families Calliphoridae and Sarcophagidae; later collectively referred to as 'carrion flies'), which are globally distributed and are known to feed on various mammalian-borne materials (carcasses, open wounds and faeces; Norris 1965).…”
Section: Introductionmentioning
confidence: 99%